Project-Based STEM Learning Integrated with Inquiry Approach to Enhance Scientific Literacy and Critical Thinking Skills in Science Education - Utami, Ayu Rischi (Scientica Education Journal, 2024)
This study aims to examine the effectiveness of project-based STEM learning integrated with an inquiry approach in improving students’ scientific literacy and critical thinking skills in science education. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The participants consisted of two groups: an experimental group taught using project-based STEM inquiry learning and a control group taught using conventional methods. Data were collected through a scientific literacy test and a critical thinking skills test. The results showed that the experimental group achieved significantly higher post-test scores compared to the control group. The normalized gain (N-gain) analysis indicated that the experimental group reached a medium to high level of improvement, while the control group remained in the low to medium category. Statistical testing using an independent sample t-test revealed a significant difference between the two groups (p < 0.05). Furthermore, the implementation of project-based STEM inquiry learning significantly enhanced students’ abilities in analysis, evaluation, and problem-solving. These findings suggest that integrating project-based learning, STEM, and inquiry approaches is an effective strategy to promote meaningful learning and develop essential 21st-century skills in science education.